HASIL BELAJAR PELAJARAN MUSIK PESERTA DIDIK DENGAN MEDIA PEMBELAJARAN BERBASI VIDEO - Brenda Evangelista; Caecilia Hardiarini (Program Studi Pendidikan Musik, 2026)
This study aims to determine the effect resulting from video-based learning media on student learning outcomes. This research was conducted at SMPN 115 Jakarta with a population of class VIII students and the sampling technique in this study was carried out using a random sampling technique. The research instrument used was pretest and posttest learning outcomes, as well as interviews with music educators. Data collection is done by conducting interviews, documentation, and observation. Meanwhile, to analyze the data, descriptive analysis and inferential analysis were carried out on the pretest and posttest learning outcomes data with the help of SPSS series 25 software. The results of this study are that there is a significant effect on video-based learning media on the learning outcomes of class VIII-E music students SMPN 115 Jakarta.